Optimizing the route for production of activated carbon from Casuarina equisetifolia fruit waste. Issue 7 (11th July 2018) - Ravichandran, P.; Sugumaran, P.; Seshadri, S.; Basta, Altaf H.
Abstract : This work deals with optimizing the conditions of pyrolysis and type of activator to upgrade the use of Casuarina equisetifolia fruit waste (CFW) as available and a potential precursor, in production of activated carbon (AC). In this respect, the route of activation was carried out through one- and two-step pyrolysis processes, using different chemical activating agents, such as H3 PO4, KOH and ZnCl2 . The performance of the CFW-based ACs is assessed by estimating the physico-chemical characteristics (pH, electrical conductivity, bulk density and hardness), surface morphology and scanning electron microscopy, together with carbon yield, surface area and adsorption performance of pollutants in aqueous medium (methylene blue, iodine and molasses colour removal efficiencies). The results show that the two-step activation process was more effective than one-step activation for providing high adsorption performance CFW-based ACs. The maximum Brunauer–Emmett–Teller surface area 547.89 m 2 g −1 was produced by using H3 PO4 activating agents, and applied two-step pyrolysis. According to the American Water Work Association and based on bulk density of the investigated ACs, we recommend that most of produced ACs are suitable for treating waste water.